Marketing Strategies for Traditional Batik Products: A Case Study of Baduy Batik - Dhany Isnaeni Darmawan; Yoga Adiyanto; Deni Sunaryo; Achmad Fazi Alam; Iman Hickmatullah (CV. Sakura Digital Nusantara, 2026)
Purpose – The purpose of this study is to analyze and formulate effective marketing strategies for Baduy Batik as a traditional cultural product in the contemporary fashion market while maintaining its cultural authenticity. The study examines the internal and external factors influencing the marketing performance of Baduy Batik and identifies strategic approaches to enhance its competitiveness. Design/methodology/approach – This study employs a qualitative case study approach. Data were collected through in-depth interviews with Baduy Batik artisans, business actors, and consumers. The collected data were analyzed using SWOT analysis to identify the key strengths, weaknesses, opportunities, and threats affecting the marketing of Baduy Batik and to formulate appropriate marketing strategies. Findings/Results – The findings indicate that the distinctive cultural identity of Baduy Batik represents its primary competitive advantage in the fashion market. However, limited market access, insufficient promotional activities, and consumer perceptions of Baduy Batik as an overly traditional product remain significant challenges. The study proposes an integrated marketing strategy that combines cultural storytelling, social media marketing, e-commerce utilization, and collaboration with fashion designers to expand market reach while preserving the traditional values embedded in the product. Originality/Value – This study contributes to the literature by demonstrating how traditional cultural products can adapt to contemporary market dynamics through innovative yet culturally sensitive marketing strategies. It also provides practical insights for artisans, policymakers, and business practitioners seeking to balance commercial development with the preservation of local cultural heritage.